Industrial concentration - Utton, M. A. (Middlesex, 1970)
This volume is one in a series of unit texts designed to reduce the price of knowledge for students of economics in universities and colleges of higher education. The units may be used singly or in combination with other units to form attractive and unusual teaching programmes. The volumes will cover the major teaching in economic areas but they will differ from conventional books in their attempt to chart and explore new directions thinking. The traditional divisions of theory and applied, of positive and normative and of micro and macro will tend to be blurred as authors impose new and arresting ideas on the traditional corpus of economics. Some units will fall into conventional patterns of thought but many will transgress established beliefs.
Keywords: Economics